SAT0380 Classification, categorisation and essential items for digital ulcer (DU) evaluation in systemic sclerosis (SSC): a desscipher/eustar survey. (15th June 2017) - Blagojevic, J; Cometi, L; Abignano, G; Guiducci, S; Bellando-Randone, S; Huscher, D; Avouac, J; Czirják, L; Denton, C; Distler, O; Frerix, M; Jaeger, VK; et al.
Abstract : Background: A consensus on DU definition in SSc has been recently reached (1), while for their evaluation, classification and categorisation it is still missing. Objectives: To identify in SSc a set of essential items for DU evaluation, to assess if the existing DU classification (2) was useful and feasible in clinical practice, and to investigate if the DU categorisation (3) was preferred to the simple division of DU in recurrent and not recurrent. Methods: The DU Desscipher items that reached >60% of completion rate were administered to EUSTAR centres via online survey.These items were: DU distal to the proximal interphalangeal joints, recurrent DU, DU history, infection, gangrene, amputation, total number of DU, number of new DU, number of healed DU, number of DU defined as loss of tissue, number of DU due to calcinosis and number of DU due to digital pitting scars (DPS).Questions about feasibility and usefulness of the existing DU classification (DU due to DPS, to loss of tissue, derived from calcinosis and gangrene) (2) and newly proposed DU categorisation (episodic, recurrent and chronic) (3) were also administered. Results: All Desscipher and 82/194 EUSTAR centres (42.3%) completed the questionnaire.Out of 27 items selected for the Desscipher study, those scored by>70% of participants as essential and feasible for DU evaluation in clinical practice were only the following: number of DU defined as a loss of tissue (level of agreement 91.1%), recurrent DU (84%) and number of new DU (74.4%).For 64.6% of the centres, the classification of DU was considered useful and feasible in clinical practice.Moreover, 80.3% of the centres preferred the categorization of DU in episodic, recurrent and chronic. Conclusions: For clinical practice, EUSTAR centres identified only three essential items for DU evaluation and considered useful and feasible the proposed classification and categorisation of DU.The set of items needs to be further validated by Delphi voting in order to implement its use in clinical practice while further implementation of DU classification and categorisation is warranted. References: Suliman Y et al.Preliminary musculoskeletal ultrasound (MSUS) ulcer definition does not correlate with visual observation in systemic sclerosis (SSc) patients. J. Scleroderma Relat. Disord.2017(in press). Amanzi L et al.Digital ulcers in scleroderma: staging, characteristics and sub-setting through observation of 1614 digital lesions. Rheumatology (Oxford) 2010;49:1374–82. Matucci-Cerinic M et al.Elucidating the burden of recurrent and chronic digital ulcers in systemic sclerosis: long-term results from the DUO Registry. Ann Rheum Dis. 2016;75:1770–6. Disclosure of Interest: None declared